The role of pH on the biological struvite production in digested sludge dewatering liquors - Simoes, Francisco; Vale, Peter C. J.; Stephenson, Tom; Soares, Ana (Nature Publishing Group, 2018)
Struvite production mediated by bacteria has opened up a new route for phosphorus recovery from wastewater streams but its application to digested sludge dewatering liquors is not yet well understood. This study investigates the growth and biological struvite production of selected bacteria in wastewater liquors with pHs between 5.7 to 9.1. The bacterial growth was assessed through flow cytometry. Bacillus pumilus, Halobacterium salinarum and Brevibacterium antiquum remained viable at pHs between 5.7 to 9.1 but B. antiquum was able to grow at pHs between 7.3 to 7.8. Further analysis allowed the identification of crystals as struvite in tests between pH 7.3 to 8.3. All strains were capable of producing struvite at a range of pHs, but the highest production of 135–198 mg/L was observed for pHs between 7.3 to 8.3. At pHs > 8.3, precipitation of struvite and calcium compounds was observed in inoculated and non-inoculated tests. This study demonstrates that biological struvite production can occur at a wide range of pHs, hence significantly different from chemical struvite precipitation that occurs at pH > 8.3, making it a potentially viable process for phosphorus recovery as struvite from wastewater streams and sludge liquors without strict pH control.